Tick-borne Disease with Yezo Virus and Borrelia miyamotoi Coinfection - Suzuki, Keiko; Suzuki, Satoshi; Yamaguchi, Hiroki; Kakinoki, Yasutaka (Internal Medicine, 2024)
Yezo virus is a novel virus transmitted by tick bites that causes fever with thrombocytopenia. To date, two reports have been published on patients with Yezo virus infection. However, the clinical characteristics of Yezo virus infection remain unclear. A patient who presented with fever, fatigue, headaches, and muscle pain and was admitted to our hospital. The patient had thrombocytopenia, leukopenia, and elevated liver enzyme and serum ferritin levels. The patient was diagnosed with Yezo virus and Borrelia miyamotoi coinfection based on the detection of Yezo virus in a blood sample by polymerase chain reaction and the detection of elevated serum antibody titers to Yezo virus and Borrelia miyamotoi.